Type-C esophageal atresia and d-transposition of the great arteries managed by a two-step sternotomy approach: A case report - Ping-Chung Tsai; Jen-Bin Wang; Shih-Yi Lo; Jun-Yen Pan (Elsevier, 2023)
Introduction: Esophageal atresia (EA) is a common congenital abnormality typically treated through a thoracotomy approach. However, the treatment can be challenging when there are associated congenital cardiovascular anomalies. Herein, we describe the case of a newborn with EA and d-transposition of the great arteries (d-TGA) successfully treated via a two-step median sternotomy approach. Case report: A newborn was born at 37 + 6 weeks gestation (weight of 2660 g) by cesarean section due to congenital heart disease. TGA was diagnosed by fetal echocardiogram. A postnatal contrast-enhanced chest computed tomography (CT) confirmed the diagnosis and additionally detected a type-C EA. The EA repair was done two days after birth via median sternotomy. An arterial switch operation for d-TGA was done twelve days after the EA repair through a repeat median sternotomy. Conclusion: This two-step approach might be suitable for selected patients who have combined congenital cardiovascular malformation and type-C EA.